Integrated calcareous nannofossil and planktonic foraminiferal bioevents of the last 1.07 Ma: a case study from the East New Zealand Pacific Ocean. - LUPI, CLAUDIA; COBIANCHI, MIRIAM; Luciani, Valeria (2008)
The core MD97-2114 (42°22.32’S; 171°20.42’W) on the northern slope of the submarine Chatham Rise (east of New Zealand, 1935m water depth), is a significant case-study for the improvement of the resolution of the mid-late Pleistocene integrated calcareous nannofossil and planktonic foraminiferal biostratigraphy. Quantitative data of calcareous nannofossils and planktonic foraminifera, well preserved and abundant throughout the core, are correlated with magnetostratigraphy and oxygen isotope stratigraphy and indicate that the studied core contains a sedimentary record of the past ca. 1.07 Ma. Several standard nannofossil events were documented and their correlation with Marine Isotope Stages (MIS) is consistent with previous calibrations. Moreover, some subsidiary events are here recorded thus improving the biostratigraphic resolution. The identification of one standard and a number of additional foraminiferal bioevents have been achieved by using climatically/ ecologically controlled entries/exits or variations in abundance. The integrated scheme obtained includes 17 bioevents, calibrated with magneto-isotope stratigraphy, and provides a biostratigraphic resolution of ca 63kyr. The bioevents of the two investigated groups of calcareous plankton appear closely spaced in two selected intervals in the lower part of the core, placed at the middle-lower part of the Brunhes Chron and at the top of the Jaramillo Subchron. The implications for the recognition of the chronostratigraphic lower-middle and middle-upper Pleistocene boundaries are discussed.